Антистерва: [роман] / А. Берсенева - Берсенева Анна (Анна Берсенева, 2018)
Перед выпускными данными автор: Анна Берсенева (Сотникова Татьяна Александровна) Экземпляры: (20181004) / Инвентарный номер: / Цена: 120.40 / Авт.знак: Б 51 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6